Global particle buildup simulations with gas puff scan: application to WEST discharge - Kudashev, I.; Scotto d’Abusco, M.; Glasser, A.; Serre, E.; Schwander, F.; Bufferand, H.; Ciraolo, G.; Ghendrih, P.; Tamain, P. (Frontiers in Physics, 2024)
This paper deals with the distribution of sources, transport and exhaust of particles in a tokamak.Knowledge and understanding of all the physical phenomena involved in the global particles buildup is necessary to study and predict density regimes, and subsequently to develop optimised scenarios for tokamak operation in order to control heat and particles exhaust. Neutral particles and their interactions with the plasma are central in this perspective. This paper discusses the impact of varying the intensity of particle fuelling in 2D transport simulations of a WEST discharge.Simulations are performed with an updated version of SOLEDGE-HDG which allows a more realistic transport of neutrals using a self-consistent diffusive model based on charge-exchange and ionization processes. New code capabilities are presented that allow the entire WEST poloidal cross-section to be simulated in a realistic configuration for both geometry and the range of control parameters. A gas puff scan illustrates reproduction by the code of the main features of the sheath-limited, high-recycling and detached regimes, such as the build-up of the temperature gradient and the pressure drop in the SOL, the target temperature falling to 1 eV, and the ionization source moving away from the targets, as well as the particle flux rollover. A crude estimate of wall erosion is also provided, showing the respective role of each plasma wall component in each of these regimes.